2001
DOI: 10.1191/026921501678310216
|View full text |Cite
|
Sign up to set email alerts
|

Walking speed over 10 metres overestimates locomotor capacity after stroke

Abstract: In our subjects after stroke, walking speed over a short distance overestimated the distance walked in 6 minutes. Both walking speed and endurance need to be measured and trained during rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(123 citation statements)
references
References 13 publications
4
114
0
5
Order By: Relevance
“…In fact, the anticipation of having more than one STS to do could explain the greater WB and effort on the nonparetic limb in the clinical test. A parallel could be made between this finding and the results of previous studies [25,26] on associations between the distance covered by poststroke individuals during the 6-or 12-minute walk tests and their self-paced gait speeds established over 8 or 10 meters. In fact, they found that using these gait speeds to predict the distances walked in either 6 or 12 minutes overestimates the actual distances covered.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In fact, the anticipation of having more than one STS to do could explain the greater WB and effort on the nonparetic limb in the clinical test. A parallel could be made between this finding and the results of previous studies [25,26] on associations between the distance covered by poststroke individuals during the 6-or 12-minute walk tests and their self-paced gait speeds established over 8 or 10 meters. In fact, they found that using these gait speeds to predict the distances walked in either 6 or 12 minutes overestimates the actual distances covered.…”
Section: Discussionsupporting
confidence: 75%
“…In fact, they found that using these gait speeds to predict the distances walked in either 6 or 12 minutes overestimates the actual distances covered. Since the gait speeds were found to be relatively constant in the functional tests, the subjects seem to pace themselves more slowly even though the instructions given are to try to cover the greatest distance in 6 or 12 minutes [25,26]. Reorganization of the task execution might thus explain why the WB and effort distributions at the knees did not change with the repetitions.…”
Section: Discussionmentioning
confidence: 98%
“…In order to evaluate gait velocity, the 10-m Walking Time (10mWT) was measured 9,10) . Patients were ask to walk as fast as possible, and the time taken to cover 10 m was measured using a stop watch.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally used for evaluation of the walking speed of patients with a neurologic deficit. In this study, the method of Dean et al 17) was used. The subjects were asked to walk at a comfortable speed for a total of 14 m. The first 2 m and the last 2 m were not timed to eliminate the effects of acceleration and deceleration.…”
Section: Methodsmentioning
confidence: 99%